Validity of Special Judo Fitness Test in Iranian Male Wrestlers. Issue 1 (2nd January 2016) - Karimi, Mohammad
ABSTRACT: In assessment of high-intensity exercise performance, strong linear relations have been found between laboratory and field measures of anaerobic fitness. The present study aimed to determine the validity of the special judo fitness test among Iranian male wrestlers. Thirty well-trained male wrestlers performed the special judo fitness test (the Ippon seoi nage technique) in 3 series of 15, 30, and 30 s with 10-s rest interval between trials. Also, a 30-s Wingate test on a cycle ergometer was used to measure anaerobic fitness in the laboratory condition. Heart rate (HR) and blood lactate concentration were measured at baseline, immediately after, and 1 min after trials. In addition, the fatigue index was calculated. Data were analyzed using a paired t test and Pearson's correlation coefficient ( p < .05). There was a significant correlation between the results of HR changes and lactate concentration changes between the two tests: r (29) = 0.88, p < .01, and r (29) = 0.89, p ≤ .01, respectively. The Bland-Altman and the intraclass correlation coefficient methods revealed medium agreement between test and retest of the special judo fitness test on test index (ICC = 0.4399; ± 1.96, 95% CI [–1.82, 2.76]). The special judo fitness test is a valid field test to assess anaerobic fitness of male wrestlers. The test can be used as a field test to evaluate anaerobic fitness in wrestling.